Management of a Failed Hybrid Implant Full-arch Prosthesis- A Case Report - Koshy, Eldo; Annamma, Lovely M; Idrissi, Hafsa Al; Abutayyem, Huda (Bangladesh Journal of Medical Science, 2024)
Background: Biological and technical hardware complications in implant-retained prostheses are well documented in the literature. The most frequently reported failures are on the immediate or delayed factors after implant placement. Even when the implant has successfully osseointegrated, there is a chance that the prosthesis can fail if the treatment planning and occlusal aspects are not well studied. Management of failed cases is rarely reported. In this case report, the authors present a failed implant prosthesis and how it was managed well with a more permanent solution. Case presentation: A 55-year-old, male retired bank manager, reported with the chief complaint of frequent fracture of the maxillary acrylic hybrid implant prosthesis that was delivered 6 months ago. He wanted a replacement for the fractured upper maxillary acrylic hybrid prosthesis. On clinical evaluation, the upper maxillary implant prosthesis was opposing the natural tooth, an anterior bridge, and two posterior implants in the lower right and left of the first and second molar region. The patient was happy with the lower restorations. Conclusion: The design of the final restoration based on biological, mechanical, technological, and patient factors should be ideally planned during the initial treatment planning stage itself. In case a prosthesis fails the underlying cause should be analyzed and retreatment planning is to be done. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 266-271